Designing Branding Kampoeng Bebek and Telur Asin Sidoarjo Kebonsari Village Based Education Tourism In An Effort To Increase Tourism Potential Tourism Village - Estherlita, Tria Kuswidya; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of designing branding Kampoeng Bebek is to increase the potential of the village as an educational tourist attraction in Sidoarjo. This research was conducted with qualitative methods obtained through the interview process, documentation, observation and study literature so that the data used is capable of supporting the creation of a design concept branding Kampoeng duck. The concept in this study were obtained from the SWOT analysis, STP, and the USP cornered back so find the keyword